2013
DOI: 10.1371/journal.pone.0055641
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Videography Method for Generating Crack-Extension Resistance Curves in Small Bone Samples

Abstract: Assessment of bone quality is an emerging solution for quantifying the effects of bone pathology or treatment. Perhaps one of the most important parameters characterising bone quality is the toughness behaviour of bone. Particularly, fracture toughness, is becoming a popular means for evaluating bone quality. The method is moving from a single value approach that models bone as a linear-elastic material (using the stress intensity factor, K) towards full crack extension resistance curves (R-curves) using a non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 27 publications
2
8
0
Order By: Relevance
“…In this study, we found it possible to document progression of crack growth during loading using very high resolution reflected white light imaging. A similar approach was also recently used to document crack extension in rat tibia [ 35 ]. While reflected white light imaging does not have the resolution of SEM, it may be advantageous for cases where a very large number of test specimens (n = 135 in this study) are needed for statistical power considerations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we found it possible to document progression of crack growth during loading using very high resolution reflected white light imaging. A similar approach was also recently used to document crack extension in rat tibia [ 35 ]. While reflected white light imaging does not have the resolution of SEM, it may be advantageous for cases where a very large number of test specimens (n = 135 in this study) are needed for statistical power considerations.…”
Section: Discussionmentioning
confidence: 99%
“…The method to calculate fracture toughness during crack initiation and growth was adapted from an approach developed by Carriero et al [ 25 ] where a crack path during mechanical loading of mouse femora was documented using environmental SEM. In this study, a high resolution imaging method was used to document the progression of crack growth, similar to the work of Katsamenis et al [ 35 ]. The projected crack extension was measured on the medial surface of the bone (Δa proj ), and this was used to calculate the instantaneous half crack angle (θ inst ), which in turn, along with the instantaneous load P, and cross sectional geometry of the bone, was used to calculate fracture toughness (K).…”
Section: Methodsmentioning
confidence: 99%
“…Fracture toughness testing was performed as previously described by (Katsamenis et al (2015); Katsamenis et al (2013)) with some modification for increased automation (primarily automatic selection of whitening area), allowing increased throughput, as indicated in Supplementary Fig. S1.…”
Section: Methodsmentioning
confidence: 99%
“…More details can be found elsewhere 1,4 . Currently bio-medical and engineering/materials science applications are the most popular, while geo-physical (see figure 3) experiments have also been carried out with great success [8][9][10][11] . Mainly pink beam is used with filtering towards higher photon energies for materials science experiments.…”
Section: Diamond-manchester Imaging Branchlinementioning
confidence: 99%